2024 ELECTIONS: GENERATING THE PEOPLE'S ECONOMY POST PANDEMI COVID 19 - Arif, Muhammad (Berpusi Publishing, 2023)
The emergence of the discourse on postponing the 2024 election has become one of the central questions at the beginning of 2021 until now. Society has many advantages and disadvantages in this regard. This is because, in addition to the provisions of the 1945 Constitution, the process of holding the 2024 elections is also taking place in the midst of post-pandemic economic recovery from COVID-19. But finally, President Joko Widodo emphasized in his speech on April 10, 2022, that the parliamentary elections in 2024 will go ahead as planned and without delay. Therefore, this study explains whether the 2024 General Election can coincide with post-COVID-19 economic recovery. By using normative legal research with qualitative data collection methods, the results of this study conclude that the 2024 election should be held in accordance with the provisions of the Constitution and can be held in the midst of post-COVID-19 economic recovery, of course with various preparations so that the 2024 general election will be held later. can also accelerate the acceleration of economic recovery due to the COVID-19 pandemic.